Meclofenamic Acid Reduces Reactive Oxygen Species Accumulation and Apoptosis, Inhibits Excessive Autophagy, and Protects Hair Cell-Like HEI-OC1 Cells From Cisplatin-Induced Damage - Li, He; Song, Yongdong; He, Zuhong; Chen, Xiaoyun; Wu, Xianmin; Li, Xiaofei; Bai, Xiaohui; Liu, Wenwen; Li, Boqin; Wang, Shanshan; Han, Yuechen; Xu, Lei; et al. (Frontiers in Cellular Neuroscience, 2018)
Hearing loss is the most common sensory disorder in humans, and a significant number of cases is due to the ototoxicity of drugs such as cisplatin that cause hair cell (HC) damage. Thus, there is great interest in finding agents and mechanisms that protect HCs from ototoxic drug damage. It has been proposed that epigenetic modifications are related to inner ear development and play a significant role in HC protection and HC regeneration; however, whether the m6A modification and the ethyl ester form of meclofenamic acid (MA2), which is a highly selective inhibitor of FTO (fatmass and obesity-associated enzyme, one of the primary human demethylases), can affect the process of HC apoptosis induced by ototoxic drugs remains largely unexplored. In this study, we took advantage of the HEI-OC-1 cell line, which is a cochlear HC-like cell line, to investigate the role of epigenetic modifications in cisplatin-induced cell death. We found that cisplatin injury caused reactive oxygen species accumulation and increased apoptosis in HEI-OC-1 cells, and the cisplatin injury was reduced by co-treatment with MA2 compared to the cisplatin-only group. Further investigation showed that MA2 attenuated cisplatin-induced oxidative stress and apoptosis in HEI-OC1 cells. We next found that the cisplatin-induced upregulation of autophagy was significantly inhibited after MA2 treatment, indicating that MA2 inhibited the cisplatin-induced excessive autophagy. Our findings show that MA2 has a protective effect and improves the viability of HEI-OC1 cells after cisplatin treatment, and they provide new insights into potential therapeutic targets for the amelioration of cisplatin-induced ototoxicity.